Fab‐Compatible Graphene: Wafer‐Scale Synthesis of Graphene on Sapphire: Toward Fab‐Compatible Graphene (Small 50/2019). Issue 50 (13th December 2019) - Mishra, Neeraj; Forti, Stiven; Fabbri, Filippo; Martini, Leonardo; McAleese, Clifford; Conran, Ben R.; Whelan, Patrick R.; Shivayogimath, Abhay; Jessen, Bjarke S.; Buß, Lars; Falta, Jens; Aliaj, Ilirjan; et al.
Abstract : In article number 1904906, Camilla Coletti and co‐workers develop an approach for directly synthesizing wafer‐scale graphene on sapphire. Thanks to the fine control of the sapphire surface, highly homogeneous wafers up to 6 in complying with fab‐requirements are obtained. This marks the dawn of a new production route for graphene.